2010
DOI: 10.3389/fnbeh.2010.00015
|View full text |Cite
|
Sign up to set email alerts
|

Learning at old age: a study on winter bees

Abstract: Ageing is often accompanied by a decline in learning and memory abilities across the animal kingdom. Understanding age-related changes in cognitive abilities is therefore a major goal of current research. The honey bee is emerging as a novel model organism for age-related changes in brain function, because learning and memory can easily be studied in bees under controlled laboratory conditions. In addition, genetically similar workers naturally display life expectancies from 6 weeks (summer bees) to 6 months (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 58 publications
(95 reference statements)
2
30
1
Order By: Relevance
“…Experimental restriction of daily flight periods further suggests that metabolically demanding flight activity is causally linked to a shortened lifespan (Neukirch, 1982), and to the agerelated decline of learning function in foragers (Tolfsen et al, 2011). Few studies so far have explored the aging dynamics of winter bees (Behrends and Scheiner, 2010;Lindauer, 1963;Seehuus et al, 2006a), but the results suggest that organismal integrity, learning and memory are not compromised despite high chronological age.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental restriction of daily flight periods further suggests that metabolically demanding flight activity is causally linked to a shortened lifespan (Neukirch, 1982), and to the agerelated decline of learning function in foragers (Tolfsen et al, 2011). Few studies so far have explored the aging dynamics of winter bees (Behrends and Scheiner, 2010;Lindauer, 1963;Seehuus et al, 2006a), but the results suggest that organismal integrity, learning and memory are not compromised despite high chronological age.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that environmental factors affect worker longevity (Seeley 1995;Remolina and Hughes 2008). Even old worker bees can display normal olfactory and tactile acquisition and discrimination, although they have a slightly impaired long-term olfactory memory (Behrends and Scheiner 2010). Simone-Finstrom and Spivak (2010) reported that social immunity is a promising area of study in social insect biology.…”
Section: Introductionmentioning
confidence: 99%
“…Age-related changes in cognitive performance of foragers have been reported in terms of a decline in the cognitive performance in older foragers that have accumulated more than 2 weeks of foraging experience (Behrends and Scheiner, 2010;Behrends et al, 2007;Scheiner and Amdam, 2009). This is interpreted as senescence caused more by the accumulated demands of foraging than chronological age, and is evidence that prolonged foraging causes cognitive ageing in a bee (Behrends and Scheiner, 2010;Behrends et al, 2007;Scheiner and Amdam, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This is interpreted as senescence caused more by the accumulated demands of foraging than chronological age, and is evidence that prolonged foraging causes cognitive ageing in a bee (Behrends and Scheiner, 2010;Behrends et al, 2007;Scheiner and Amdam, 2009). In our experiments, foraging experience was not precisely controlled and therefore could cognitive decline explain the difference in performance between precocious and normal-aged foragers?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation